2011
DOI: 10.1136/oem.2010.064097
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in occupational exposure patterns

Abstract: Objectives:We conducted a population-based survey to examine gender differences in occupational exposure patterns and to investigate whether any observed differences are due to: a) gender differences in occupational distribution; and/or b) gender differences in tasks within occupations. Methods:Men and women aged 20-64 years were randomly selected from the Electoral Roll and invited to take part in a telephone interview, which collected information on selfreported occupational exposure to specific dusts and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 13 publications
7
113
0
9
Order By: Relevance
“…It has been noted that working and general populations of women differ in risk factors (Bond et al, 1987) and female and male employees in the same industry may have different tasks even if they have the same job title (Stellman, 1999). The observed mortality differences between male and female workers may be due to differences in work assignments, differences in physiology, and differences in how their bodies reacted to PCBs (Eng et al, 2011;Messing and Mager Stellman, 2006;Silvaggio and Mattison, 1994). Since various PCB congeners have estrogenic, anti-estrogenic, androgenic or anti-androgenic properties (Diamanti-Kandarakis et al, 2009), it follows that female-male hormonal differences might be associated with the activity of PCBs in the body (Meeker and Hauser, 2010;Salehi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that working and general populations of women differ in risk factors (Bond et al, 1987) and female and male employees in the same industry may have different tasks even if they have the same job title (Stellman, 1999). The observed mortality differences between male and female workers may be due to differences in work assignments, differences in physiology, and differences in how their bodies reacted to PCBs (Eng et al, 2011;Messing and Mager Stellman, 2006;Silvaggio and Mattison, 1994). Since various PCB congeners have estrogenic, anti-estrogenic, androgenic or anti-androgenic properties (Diamanti-Kandarakis et al, 2009), it follows that female-male hormonal differences might be associated with the activity of PCBs in the body (Meeker and Hauser, 2010;Salehi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…29 These characteristics may be related to increased exposure or the hazards experienced by females or those working in school settings. Earlier authors 31 found differences in occupational exposures between men and women within the same occupation. These differences may also reflect the ability or tendency (or both) to report injuries by sex and work setting.…”
Section: Discussionmentioning
confidence: 91%
“…Женщины более часто трудо-устраиваются на неполный рабочий день, в свою оче-редь, мужчины чаще работают в условиях физических нагрузок, под воздействием высоких уровней шума и/ или вибрации, а также при более длительном рабочем дне и на более высоких должностях [16]. Даже в пределах одних и тех же профессиональных групп мужчины харак-теризуются более выраженным воздействием неблаго-приятных физических факторов, ночными сменами и нерегулярной работой [17]. В результате, зачастую, мужчины продолжают трудовую деятельность даже в условиях серьезных нарушений состояния здоровья, при которых женщины прекращают трудовую деятель-ность.…”
Section: Discussionunclassified